Sierpinski Mimo Antenna For 5G Applications - Mousa, Ali Hasan; Othman, Mohd Azlishah; Abd Aziz, Mohamad Zoinol Abidin; Mohammed Ibrahim, Ayman (Wydawnictwo SIGMA-NOT, 2021)
A Sierpinski MIMO antenna was designed in the band of 3.4 – 3.8 GHz for 5G communications is demonstrated in this paper. The proposed antenna is printed on a FR_4 substrate material and dimension of the antenna was 20 × 25 × 0.8 mm3. This paper presents the development of a compact MIMO antenna using a new structure integrated with the Sierpinski using neutralization line and defected ground structure techniques for mutual coupling reduction and antenna isolation improvement. The simulated results proved that the proposed method gives an excellent isolation performance. A good impedance matching return loss of large than 10 dB, high isolation of large than 22 dB at the operating frequency, and low ECC that was 0.026 was simulated across the coveted operating bandwidth.